3D‐Printed Phenacrylate Decarboxylase Flow Reactors for the Chemoenzymatic Synthesis of 4‐Hydroxystilbene - Peng, Martin (Chemistry, 2019)
Continuous flow systems for chemical synthesis are becoming a major focus in organic chemistry and there is a growing interest in the integration of biocatalysts due to their high regio‐ and stereoselectivity. Methods established for 3D bioprinting enable the fast and simple production of agarose‐based modules for biocatalytic reactors if thermally stable enzymes are available. We report here on the characterization of four different cofactor‐free phenacrylate decarboxylase enzymes suitable for the production of 4‐vinylphenol and test their applicability for the encapsulation and direct 3D printing of disk‐shaped agarose‐based modules that can be used for compartmentalized flow microreactors. Using the most active and stable phenacrylate decarboxylase from Enterobacter spec. in a setup with four parallel reactors and a subsequent palladium(II) acetate‐catalysed Heck reaction, 4‐hydroxystilbene was synthesized from p‐coumaric acid with a total yield of 14.7 % on a milligram scale. We believe that, due to the convenient direct immobilization of any thermostable enzyme and straightforward tuning of the reaction sequence by stacking of modules with different catalytic activities, this simple process will facilitate the establishment and use of cascade reactions and will therefore be of great advantage for many research approaches.